Experimental phase equilibria of the system Cu–O–CaO–Al2O3 in air. Issue 3 (February 2016) - Hamuyuni, Joseph; Taskinen, Pekka
Abstract: Phase equilibria of the system Cu–O–CaO–Al2 O3 at Po2 of 21278.25 Pa was experimentally investigated for the first time using equilibration techniques. Composition of glassy molten phase and all solids in equilibrium were quantified using Electron Probe Micro-Analyzer (EPMA). Isothermal ternary sections of the 'Cu2 O'–CaO–Al2 O3 system in the temperature range 1150–1400 °C in steps of 50 °C have been constructed based on three phase equilibria experimental data. From the triple points data obtained, large deviations exist among previously thermodynamically assessed diagrams and experimental results of this study. Especially triple points one (1), with halite and tricalcium aluminate as solid phases, and triple point four (4), with monocalcium aluminate and monocalcium dialuminate as solid phases, between 1350 and 1400 °C, where the deviations in Al2 O3, 'Cu2 O' and CaO contents of the liquid phase reach 40 wt%. Thus there is a need for re-assessment with the new experimental data.